MORPHOLOGICAL IDENTIFICATION OF FUNGAL PATHOGENS ASSOCIATED WITH POST-HARVEST DISEASES - Ulilalbab, Azizah Ridha; Cahyasita, Dhika; Pratiwi, Nova Wahyu; Ajri, Miftahul; Hanikaf, Uliyatul Muhmiroh; Kuncoro, Seto Agung (Jurnal Agrivet, 2023)
Post-harvest products are perishable and vulnerable to diseases that lead to quality deterioration and yield loss. One of the primary diseases found in most post-harvest products is caused by fungal pathogens. This study identified fungal pathogens associated with post-harvest products through morphological characterization. Fruit and vegetable samples were collected from traditional markets and fruit stores in Central Java. The results of fungal pathogens identification causing disease on post-harvest products showed that Pestalotiopsis sp and Neopestalotiopsis sp. were found on guava with white blackish mycelium, present concentric ring and blackspot, Aspergillus sp. on tomato with yellow-greenish mycelium, present concentric ring only, Botrytis sp. with grey mycelium and Rhizoctonia solani with white greyish mycelium and present of a concentric ring on apple, Rhizoctonia solani with greyish black and present of blackspot on mango, and Colletotrichum sp. with white greyish mycelium and present of a concentric ring, conidiomata and blackspot on citrus. This study concluded that the most fungal pathogens on post-harvest that we found were Pestaloptia sp., Rhizoctonia solani, Aspergillus sp., Botrytis sp., and Colletotrichum sp.